2000
DOI: 10.1099/00221287-146-9-2113
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphosphorylation of Msn2p and Msn4p in response to heat shock and the diauxic shift is inhibited by cAMP in Saccharomyces cerevisiae

Abstract: In response to various stresses, as well as during the diauxic transition, the Msn2p and Msn4p transcription factors of Saccharomyces cerevisiae are activated and induce a large set of genes. This activation is inhibited by the Ras/cAMP/PKA (cAMP-dependent protein kinase) pathway. Here we show by immunoblotting experiments that Msn2p and Msn4p are phosphorylated in vivo during growth on glucose, and become hyperphosphorylated at the diauxic transition and upon heat shock. This hyperphosphorylation is correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
2
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 31 publications
7
111
2
2
Order By: Relevance
“…To further test whether the observed slowdowns in nuclear translation, phosphorylation and protein mobility were specific to components of the HOG pathway, we examined the dynamics of the nuclear translocation of Msn2p (34)(35)(36), a key transcription factor in the general stress response of yeast. After hyperosmotic stress, Msn2p is hyperphosphorylated and imported into the nucleus (37).…”
Section: Resultsmentioning
confidence: 99%
“…To further test whether the observed slowdowns in nuclear translation, phosphorylation and protein mobility were specific to components of the HOG pathway, we examined the dynamics of the nuclear translocation of Msn2p (34)(35)(36), a key transcription factor in the general stress response of yeast. After hyperosmotic stress, Msn2p is hyperphosphorylated and imported into the nucleus (37).…”
Section: Resultsmentioning
confidence: 99%
“…Upon glucose exhaustion, they are hyperphosphorylated and translocated to the nucleus, where they induce expression of the STREcontrolled genes. PKA inhibits nuclear import of Msn2/4, probably through direct phosphorylation of their nuclear localization signal (Gorner et al 1998(Gorner et al , 2002Garreau et al 2000). A second mechanism for PKA-mediated regulation of STRE-controlled gene expression involves the Ccr4-Not complex, a global transcriptional regulator that affects genes positively and negatively.…”
Section: Regulation Of the Camp-pka Pathwaymentioning
confidence: 99%
“…On the other hand, TORC1 inhibits the transcription of stress-responsive genes via a Rim15-independent, but Tap42-PP2A-dependent route, thereby promoting the phosphorylation and cytoplasmic retention of Msn2 (Beck and Hall 1999; Duvel et al 2003;Santhanam et al 2004). It is important to note that the latter is independent of the PKA-mediated phosphorylation of the Msn2/4 nuclear localization signal (Gorner et al 1998(Gorner et al , 2002Garreau et al 2000;Santhanam et al 2004).…”
Section: Rapamycin-sensitive Signalling Via Torc1mentioning
confidence: 99%
“…Therefore, we examined whether yeast GSK-3 phosphorylates Msn2p in intact cells. It has been shown that heat shock and glucose starvation induce a mobility shift of Msn2p on an SDS gel, which reflects the phosphorylation of Msn2p (Garreau et al, 2000). After the wild-type strain and the gsk-3 null mutant had been subjected to salt stress, the yeast extracts were electrophoresed and probed with the anti-Myc antibody to detect Msn2p.…”
Section: Possible Mechanism Of Regulation Of Msn2p By Gsk-3mentioning
confidence: 99%